2016
DOI: 10.1097/md.0000000000003480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Anticoagulation Therapy in Patients With Symptomatic Spontaneous Isolated Dissection of the Superior Mesenteric Artery

Abstract: The aim of this study was to determine the clinical outcomes of long-term anticoagulation therapy in patients with symptomatic spontaneous isolated dissection of the superior mesenteric artery (SIDSMA) and to evaluate whether conservative treatment with anticoagulation therapy is a safe and effective treatment modality for these patients.In this single center, observational cohort study, data from a prospectively recruiting symptomatic SIDSMA registry, including demographics, risk factors of interest, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 20 publications
2
47
1
1
Order By: Relevance
“…The management strategies were determined according to the patients' symptoms and signs, as well as the initial CTA findings. Conservative medical treatment, which consisted of pain management, strict hypertension control (target systolic and diastolic blood pressures < 140 and < 90 mmHg, respectively), 6 bowel rest, intravenous fluid therapy, nutritional support, and close observation, was initially administered to all patients. Systemic anticoagulation with intravenous heparin followed by oral warfarin therapy was provided for selected patients (78%, 18/23), and anticoagulation was typically continued for 6 months to achieve a target international normalised ratio of 2.0e3.0.…”
Section: Diagnostic Work Up and Management Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The management strategies were determined according to the patients' symptoms and signs, as well as the initial CTA findings. Conservative medical treatment, which consisted of pain management, strict hypertension control (target systolic and diastolic blood pressures < 140 and < 90 mmHg, respectively), 6 bowel rest, intravenous fluid therapy, nutritional support, and close observation, was initially administered to all patients. Systemic anticoagulation with intravenous heparin followed by oral warfarin therapy was provided for selected patients (78%, 18/23), and anticoagulation was typically continued for 6 months to achieve a target international normalised ratio of 2.0e3.0.…”
Section: Diagnostic Work Up and Management Strategymentioning
confidence: 99%
“…Full anticoagulation with intravenous heparin followed by oral warfarin therapy was administered in all patients with SSMAD immediately after the diagnosis. 6…”
Section: Outcomes Of Interest and Follow Upmentioning
confidence: 99%
“…Treatment options include blood pressure control, antiplatelet therapy, anticoagulation, endovascular stenting, and surgical repair. 7 There have been published reports advocating for both conservative 4,8 and invasive 9 interventions. Optimal medical therapy is also disputed; there is no consensus regarding antiplatelet therapy versus anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…In general, some combination of antihypertensive, anticoagulation, or antiplatelet drug therapy is recommended. 16 Many authors reported good outcomes using anticoagulation therapy, 9,17 and some have called for anticoagulation as first-line therapy. 18 We found that in symptomatic patients without evidence of ischemia, there was no significant difference in occurrence of LVT or aneurysm in patients treated with medical management vs observation alone.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent treatment recommendations for symptomatic and asymptomatic patients vary on the basis of the experiences of individual institutions and have been supported mostly by small retrospective reviews and a few larger retrospective reviews. [7][8][9][10][11] Suggested treatments include medical management with or without anticoagulation, surgery, and endovascular intervention. Whereas indications for immediate intervention can be self-evident, the optimal treatment is uncertain for patients with anything less than significant end-organ ischemia.…”
mentioning
confidence: 99%